Microwave-assisted urea catalyzed Knoevenagel condensation of aldehydes with active methylene compounds - Purba, WT; Roy, PS; Jannat, S; Begum, SA; Rahman, MM (Bangladesh Journal of Scientific and Industrial Research, 2020)
Rapid and efficient method for the synthesis of substituted olefins such as 2-(4-chlorophenylmethylene) malononitrile, 2-(4-hydroxyphenylmethylene) malononitrile and 2-cyano-3-(4-hydroxyphenyl) acrylamide etc under the influence of microwave irradiation are described. Urea has been utilized as an efficient catalyst for the Knoevenagel condensation of aldehydes with acidic active methylene compounds such as malononitrile, ethylcyanoacetate and cyanoacetamide to afford substituted olefins under the influence of microwave irradiation. The reaction proceeds smoothly under mild and solvent free conditions and the products are obtained in good yield. The method is applicable for a wide range of aldehydes including aromatic and heterocyclic substrates. Bangladesh J. Sci. Ind. Res.55(2), 159-164, 2020